Dietary lysophosphatidylcholine-EPA enriches both EPA and DHA in the brain: potential treatment for depression[S] - Yalagala, PoornaC.R.; Sugasini, Dhavamani; Dasarathi, Sridevi; Pahan, Kalipada; Subbaiah, Papasani V. (Journal of lipid research, 2019)
EPA and DHA protect against multiple metabolic and neurologic disorders. Although DHA appears more effective for neuroinflammatory conditions, EPA is more beneficial for depression. However, the brain contains negligible amounts of EPA, and dietary supplements fail to increase it appreciably. We tested the hypothesis that this failure is due to absorption of EPA as triacylglycerol, whereas the transporter at the blood-brain barrier requires EPA as lysophosphatidylcholine (LPC). We compared tissue uptake in normal mice gavaged with equal amounts (3.3 μmol/day) of either LPC-EPA or free EPA (surrogate for current supplements) for 15 days and also measured target gene expression. Compared with the no-EPA control, LPC-EPA increased brain EPA >100-fold (from 0.03 to 4 μmol/g); free EPA had little effect. Furthermore, LPC-EPA, but not free EPA, increased brain DHA 2-fold. Free EPA increased EPA in adipose tissue, and both supplements increased EPA and DHA in the liver and heart. Only LPC-EPA increased EPA and DHA in the retina, and expression of brain-derived neurotrophic factor, cyclic AMP response element binding protein, and 5-hydroxy tryptamine (serotonin) receptor 1A in the brain. These novel results show that brain EPA can be increased through diet. Because LPC-EPA increased both EPA and DHA in the brain, it may help in the treatment of depression as well as neuroinflammatory diseases, such as Alzheimer's disease.